Methodical aspects of the development of scientific speech in non-philological university students - Marziyat Kaseevna Tlekhuraih (Вестник Майкопского государственного технологического университета)
In modern conditions training of highly qualified specialists is not possible without a thorough training of their Russian language. The discipline “The Russian language and culture of speech” includes a section devoted to the functional and style differentiation of the modern Russian literary language. The study of the scientific style of speech is an important part of the “Russian Language and Speech Culture” course. The relevance of the study of scientific speech is justified by the fact that at the present stage of society development in the context of an intensive increase in the volume of scientific knowledge and development of various fields of science and technology, there is an urgent need for the exchange of relevant scientific information. The research problem is consideration and analysis of specific features and functions of the scientific style, situations of scientific communication and methodological aspects of teaching the scientific style of students in a non-philological university. The purpose of the research is to review and analyze scientific and methodological literature, as well as the degree of development of the methodology for the studied problems. According to the results of the research, it can be concluded that the introduction of active communicative teaching methods and techniques in the educational process, both written and oral scientific speech, will qualitatively increase the level of Russian language proficiency of future specialists.